Ultrasonic Thickness of Lateral Abdominal Wall Muscles in Response to Pelvic Floor Muscle Contraction in women with stress incontinency with and without Chronic Low Back Pain - Farideh Dehghan-Manshadi; Roxana Bazaz-Behbahani; Khosrow Khademi; Maryam Rahmani; Tahereh Eftekhar (University of Social Welfare and Rehabilitation Sciences, 2014)
Objective: Urinary Incontinence (UI) as a common lower urinary tract dysfunction , results from Pelvic Floor Muscle's (PFM) underactivity.Because of co-activation of PFM and the Lateral Abdominal Wall Muscles (LAWM), this study was aimed to investigate the changes in the ultrasonic thickness of the LAWM in response to PFM contraction in stress urinary incontinent (SUI)women with and without Chronic Low Back Pain (CLBP). Materials & Methods: A total of 28 women, 10 healthy, 18 SUI with and without CLBP (9 in each group) participated in this quasi-experimental study. After collecting demographic information and assessment of PFM function, changes in ultrasonic thickness of right LAWM were measured in response to PFM contraction. One way ANOVA, Kruskal-Wallis and Pearson's correlation tests were performed to analyze the data. Values of P<0.05 were considered statistically significant. Results: No significant difference was found in thickness of the LAWM while PFM were at rest (P>0.05). There was a significant increase in thickness of the Traversus Abdominis Muscle (TrA) during PFM contraction in control group comparing experimental groups (P=0.03). Women in control group showed significantly higher PFM strength and more intravaginal pressure (P=0.001). Conclusion: Changes in ultrasonic thickness of the TrA during PFM contraction revealed disturbance of co-activation of the LAWM and the PFM in women with and without SUI CLBP.